Lacas, dorados y enconchados de la tierra. Artistas, materiales locales y objetos de inspiración asiática en la Amazonía de Brasil - Renata Maria de Almeida Martins (Nuevo mundo - Mundos Nuevos, 2025)
Objects of Asian inspiration crossed oceans, continents including America, spreading the taste for silks, porcelain and lacquers, when they were originally reinvented in pieces produced by indigenous, African and mestizo artists, with materials from the land. This category of objects had an important reception and diffusion in 18th century Brazil, as they found dialogue with ancestral Amerindian traditions, in the sophisticated work of local artists, sculptors and painters, men and women. Thus, traditional objects from indigenous cultures, such as cuias (fruits of the cuieira, Crescentia cujete), were endowed with new meanings and/or prepared for export, based on coincidences in the artistic field, such as the use of black varnish made from the bark of the cumatezeiro (Myrcia atrametifera) by indigenous women from the Amazon, compared to the best lacquer from China (Rhus vernicifera or Rhus verniciflua). In turn, knowledge of motifs arising from the Asian repertoire, through the circulation of porcelain and textiles, was reflected in furniture and decoration. The cases to be presented in the Brazilian Amazon – by means of the study of documents and collections – reflect the development of powerful interconnections between America and Asia, as well as appropriations, disputes and resistance.